Soil phytotoxicity assessment with different types of anthropogenic pollution - Saranenko, I. I. (Man and Environment. Issues of Neoecology, 2025)
Purpose. Determination of soil phytotoxicity in various sites through bioassay using seeds of garden cabbage (Brassica oleracea L.), common bell pepper (Capsicum annuum L.), and garden radish (Raphanus sativus L.).Methods. Analytical, field research, biotesting, statistical.Results. It was found that the test site near the landfill is heavily polluted: the phytotoxic effect (PE) reaches 69,6%, indicating significant growth suppression, with soil solution pH of 4,9. The soil along the roadside is polluted above the average level, showing a maximum PE of 53,4% for sweet pepper seed germination, with a pH of 4,9. The sample from the agricultural field showed a moderate phytotoxic effect, with a pH of 5,4. The control site showed a high germination rate without signs of phytotoxicity, with a pH of 4,9. In all contaminated areas, an acidic soil environment with pH 4,5–5,4 was formed in the 0–20 cm layer. At such values, most nutrients become poorly available to plants. Characteristic morphological signs of toxic stress are observed: leaf curling, edge whitening, and root deformation. The greatest sensitivity to contamination was shown by sweet pepper seeds (Capsicum annuum L.).Conclusions: It were indicated that technogenically loaded soils have a negative impact on seed germination and further development. Biotesting proved to be an effective method of preliminary bioindicative monitoring of soil conditions and can be recommended for use in communities and educational institutions to identify hidden environmental threats.